Kaltim Today's Organizational Communication Ambience in Producing Quality Journalistic (Universitas Terbuka, 2025)
This study examines the organizational communication climate in the online media Kaltim Today, which contributes to the production of quality journalism. Communication patterns involve direct information delivery from management to employees, particularly journalists, particularly in situations requiring a rapid response. Horizontal communication also exists between employees to coordinate tasks, particularly in the editorial department. Therefore, the communication climate is measured through five values: support, participatory decision-making, trust, openness and sincerity, and high-performance goals. Findings indicate that despite leadership support, openness between employees and management remains a concern. Decision-making tends to be centered on management, and the company faces challenges in establishing a clear vision, mission, and standard operating procedures. Recommendations for improving the organizational communication climate include increasing subordinate involvement in decision-making, addressing transparency issues, designing a vision and mission statement involving employees, and improving structured communication management. These steps are expected to strengthen the communication climate, improve the quality of journalistic products, and support the achievement of company goals. The research method used is qualitative with a descriptive approach, where data is collected through interviews, observation, and documentation. Informants include the editor-in-chief, journalists with young competency status, and employees from various fields at Kaltim Today.